Bipolar affective disorder with co-morbid substance abuse in relation to criminal offending - Sorketti, E.A. (http://www.arabpsynet.com/, 2009)
High rates of co-morbid alcohol and drug disorders have previously been found among individuals with severe mental illnesses such as schizophrenia and bipolar affective disorders. Clinical and social outcomes have been reported to be worse in this group and service costs greater than in individuals with severe mental illness only. Men with schizophrenia who also had a record of substance misuse were over eight times more likely to appear among the violent offenders, and four times more likely to be convicted of homicide, than those without co morbid substance misuse. A similar pattern was found in affective disorders. The prevalence of substance problems among people suffering from severe mental disorders is high, and seems to be associated with greater use of in-patient services and also associated with higher rate of criminal offending.Research has indicated that patients with severe mental illnesses, such as schizophrenia or bipolar affective disorder, have high rates of concurrent mental and behavior disorders due to misuse of alcohol and non-prescribed drugs. Clinical and social outcomes may be significantly worse than in those with severe mental illness alone. They also have substantially higher rates of offending and imprisonment.